2010
DOI: 10.1007/s10439-010-0158-4
|View full text |Cite
|
Sign up to set email alerts
|

Biotransport Phenomena in Freezing Mammalian Oocytes

Abstract: Water transport across the cell plasma membrane and intracellular ice formation (IIF)-the two biophysical events that may cause cell injury during cryopreservation-were studied by cryomicroscopy and modeling using mammalian (Peromyscus) oocytes. Unusually high activation energy for water transport across the cell plasma membrane was identified indicating that the water transport process is unusually sensitive to temperature (and cooling rate). Although literally all studies on IIF were conducted using protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 63 publications
(56 reference statements)
0
24
0
Order By: Relevance
“…IIF could be due to both surface-catalyzed nucleation (SCN) and volume-catalyzed nucleation (VCN) [31,43,44]. Therefore, the tumor damage could be determined by the probability of ice formation (PIF) as a result of both SCN and VCN as follows [44,45]:…”
Section: Intracellular Ice Formation (Iif) During Freezingmentioning
confidence: 99%
See 1 more Smart Citation
“…IIF could be due to both surface-catalyzed nucleation (SCN) and volume-catalyzed nucleation (VCN) [31,43,44]. Therefore, the tumor damage could be determined by the probability of ice formation (PIF) as a result of both SCN and VCN as follows [44,45]:…”
Section: Intracellular Ice Formation (Iif) During Freezingmentioning
confidence: 99%
“…where B is cooling rate in C min À1 ,t is time, T 0 is the equilibrium freezing temperature under isotonic solutions (À0.5 C), A and V are cell surface area and volume, respectively, I SCN and I VCN are nucleation rates which are calculated as follows [44,45]:…”
Section: Intracellular Ice Formation (Iif) During Freezingmentioning
confidence: 99%
“…The two model parameters (constants) under isotonic solution state (Ω 0 and κ 0 ) need to be determined a priori by experimental studies and have been reported in the literature for a number of cell types as summarized elsewhere (He and Bischof 2003;Toner 1993;Yang et al 2010b). The cumulative probability of intracellular ice formation (P IIF ) can then be calculated as follows (Toner 1993;Toner et al 1990):…”
Section: Biophysics In Cell Preservationmentioning
confidence: 99%
“…Significant IIF is usually manifested as darkening of the cell cytoplasm when observed under a bright field of light microscopy, which has been used widely to quantify the kinetics of IIF (Diller 2005;Toner et al 1991;Yang et al 2010b). …”
Section: Biophysics In Cell Preservationmentioning
confidence: 99%
See 1 more Smart Citation